How far are we from possible ideal virtual water transfer? Evidence from assessing vulnerability of global virtual water trade - Du, Yueyue; Fang, Kai; Zhao, Dandan; Liu, Qingyan; Xu, Zihan; Peng, Jian (The Science of the total environment, 2022)
With the increasing contradiction between water demand and supply in a telecoupled society where nature and human interplay intensively over distance, virtual water trade (VWT) plays an indispensable role in global water use sustainability. There has been little quantitative analysis of global water use sustainability depicting both overall system characteristics and flows between subsystems. In such a context, the extent to which virtual water transfer deviates from possible ideal expectations (i.e., virtual water flows from water-abundant regions to water-scarce ones), and its impact on global water use sustainability, are not well evaluated. Therefore, the global VWT vulnerability framework is proposed to delineate the gap between the real VWT and the possible optimal scenario, providing potential space for future optimization and regulation. Represented by the ratio of weighted total virtual water volume to the original one, the vulnerability is assessed from 2005 to 2015 based on the Eora input-output database and Virtual Water Transfer Multiplier which assigns differentiated weights to per unit volume of virtual water transfer based on the water stress levels of importers and those of exporters. Results show that the global VWT vulnerability has increased by 18.9% during the study period, with Africa and Southern and Central Asia making the biggest contribution. Developed countries contributed around 80% of the increased global VWT vulnerability. However, the proportion has fallen a bit, in terms of the conventional view of developed countries taking the approach of transferring responsibility to developing countries. Instead, the proportions of transferring responsibility between developing countries have rose by 10% to 30% during 2005–2015, partially due to stronger trade ties among developing countries. Our findings support policy decisions on tracing environmental responsibility for water scarcity and call for action to prevent water ecological downsides due to international trade. [Display omitted] •Vulnerability of global virtual water trade is proposed to assess sustainability.•Overall system features and interactions between subsystems are both quantified.•National and regional contribution to global VWT vulnerability is evaluated.•Shared responsibility for national contribution to global VWT vulnerability is tracked.•Shifting responsibility from developed to developing countries is common but weakened.